Other voices from Pakistan (New Delhi, 1996)
The present collection of essays, news reports and literary pieces by Pakistani writers is an attempt to break through the bureaucratic smokescreen put up by both New Delhi and Islamabad to keep the people of the two countries apart. It conveys to Indian readers the other voices from Pakistan voices in which many Indians will find echoes of their own concerns, and a belief in causes which they share-defence of democratic rights. assertion of women's freedom. protection of the cultural identity of minority communities, curbing of religious intolerance, reduction in defence expenditure and friendship between India and Pakistan. It brings home to Indian readers reports of the struggles being fought by men and women in Pakistan against repressive laws, Islamisation. militarisation and other forms of injustice.
Keywords: India-Politics and Government-1995